Traffic classification model based on fusion of multiple classifiers with flow preference - Shi DONG; Wei DING (Tongxin xuebao)
The concept of multi-classifier fusion was introduced which can improve the classification accuracy and over-come the disadvantage of single classifier.DS theory was introduced into decision module of traffic classification and preference and timeliness was proposed.After analyzing multi-classifier model by simulation,the results show the new classifier model can overcome one sidedness of single ier,depending on multiple evidences to optimize the traffic results.